2018
DOI: 10.18535/ijsshi/v5i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Information Technology, Satisfaction and Motivation to Teacher Performance

Abstract: This study aims to determine the effect of information technology, satisfaction and motivation on teacher performance. Respondents are civil servant teachers of Public Elementary School in Kendit sub-district, Situbondo district, amounting to 104 teachers, which amounts to 104 teachers. The sample size is 83 people. Research using multiple linear regression analysis. The research findings show that there is no influence between information technology variables on teacher performance. While the variable of sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
1
5
0
2
Order By: Relevance
“…The statistical T value is smaller than the T table (1.486 <1.984) and the P value of 0.138 or greater than the 5% alpha standard (0.138 <0.05) indicates that motivation is not able to provide a moderating effect on academic supervision of performance quality. This result at the same time rejects the findings (Farida et al, 2020;Rasyid & Tanjung, 2020;Siahaan et al, 2020;Wahyudi et al, 2018).…”
Section: The Role Of Moderation Of Motivation In the Relationship Of Academic Supervision On The Quality Of School Performancesupporting
confidence: 60%
“…The statistical T value is smaller than the T table (1.486 <1.984) and the P value of 0.138 or greater than the 5% alpha standard (0.138 <0.05) indicates that motivation is not able to provide a moderating effect on academic supervision of performance quality. This result at the same time rejects the findings (Farida et al, 2020;Rasyid & Tanjung, 2020;Siahaan et al, 2020;Wahyudi et al, 2018).…”
Section: The Role Of Moderation Of Motivation In the Relationship Of Academic Supervision On The Quality Of School Performancesupporting
confidence: 60%
“…Generally, it is reasonable to expect that aging and work experiences can increase the amount of knowledge and, thus, expertise. Ericsson and Matthews et al, [17,31]. have indicated that this should be true for routine expertise in the context of expert-novice differences, considering the domain-speci c experience, as experience causes autonomous skill execution through practice.…”
Section: Adaptive Expertise and Experiencementioning
confidence: 99%
“…Consensus on how work experience in uences adaptive expertise is a question. Ericsson [31] and Grunefeld [34] reviewed several research studies and indicated that a signi cant correlation was not always observed between the amount of professional experience or professional training and work performance. Furthermore, they reported a signi cant negative correlation between length of experience and objective performance, stating that performing tasks of highly experienced persons are not always superior to that of students using examples from the elds of computer programming and physics [31].…”
Section: Adaptive Expertise and Experiencementioning
confidence: 99%
“…Perubahan perilaku karena teknologi telah menghasilkan kinerja individu yang lebih berkualitas di sebuah organisasi. Temuan-temuan tersebut telah dikemukaan oleh (Abusharbeh & Nazzal, 2018); (Bao & Nizam, 2015); (Andriana, 2015); (Wahyudi et al, 2018) yang mengatakan bahwa motivasi kerja mempunyai dampak atas kinerja individu, temuan lain yang dikemukakan oleh (Igbaria & Tan, 1997); (Hasiholan, 2005); (Salamah, 2012) juga mengatakan bahwa penggunaan teknologi informasi memiliki pengaruh positif atas kinerja individu.…”
Section: Pendahuluanunclassified
“…Dari hasil pengujian hipotesis yang sudah dilakukan memperlihatkan bahwa motivasi kerja petani mempunyai dampak positif atas kinerja petani sehingga hipotesis 1 diterima. Hasil temuan ini memperkuat kajian yang pernah dikerjakan oleh (Abusharbeh & Nazzal, 2018); (Bao & Nizam, 2015); (Andriana, 2015); (Wahyudi et al, 2018). Dengan mengacu pada teori harapan, maka setiap individu berupaya untuk mencapai atau memenuhi harapannya tersebut yang nantinya akan bertujuan untuk meningkatkan kinerja individu (Suripto, 2016).…”
Section: Pembahasanunclassified